Функції і види повторів у творах французьких поетів - Костюк, Марина Миколаївна; Kostiuk, M. M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті всебічно проаналізовано функції повторів у поезії французьких поетів кінця ХІХ ст. Виділено два основних види повторів – звукові та синтаксичні. Серед звукових повторів проаналізовано евфонічні й метричні повтори. У статті з’ясовано основні функції та ознаки синтаксичних повторів. Кожна функція повторів проілюстрована яскравим прикладом із французької поезії кінця ХІХ ст. In this article the types and functions of repetition in the poetry of French writers of the XIX century are analysed. It defines two main types of repetition – sound and syntax. It analyses the euphonic (rhyme, alliteration, assonance, dissonance, parallel constructions) and metric repetitions in the poetry. In the article the basic functions and features of syntactic repetition are identified. Among the main functions of repetitions it analyzes the technique of focusing reader’s attention, creating a special rhythm in the verse, highlighting some important ideas of the poem, accentuation of important images and some others. Each function is illustrated by the vivid example from the French poetry of the late nineteenth century.
Functions and Types of Repetitions in the Works of French Poets
Keywords: повтор; repetition; евфонія; euphony; рима; rhyme